2023
DOI: 10.1073/pnas.2211625120
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen stable isotope probing of lipids demonstrates slow rates of microbial growth in soil

Abstract: The rate at which microorganisms grow and reproduce is fundamental to our understanding of microbial physiology and ecology. While soil microbiologists routinely quantify soil microbial biomass levels and the growth rates of individual taxa in culture, there is a limited understanding of how quickly microbes actually grow in soil. For this work, we posed the simple question: what are the growth rates of soil microorganisms? In this study, we measure these rates in three distinct soil environments using hydroge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 95 publications
(167 reference statements)
0
21
0
Order By: Relevance
“…In a recent survey it was demonstrated that aw can range from values close to 0.1 up to values close to 1 (76). In complex communities, such as soil, the assimilation constant is difficult to estimate, but assuming all microbes are heterotrophs, this value is on average 0.71 (35), which we also applied in this study. However, it is important to note that using a different aw factor could lead to strong changes in the final quantification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent survey it was demonstrated that aw can range from values close to 0.1 up to values close to 1 (76). In complex communities, such as soil, the assimilation constant is difficult to estimate, but assuming all microbes are heterotrophs, this value is on average 0.71 (35), which we also applied in this study. However, it is important to note that using a different aw factor could lead to strong changes in the final quantification.…”
Section: Discussionmentioning
confidence: 99%
“…FA representing the natural 2 H abundance of the same fatty acid (sample taken from the same plot and incubated with natural abundance water), at%soil water indicating the 2 H atom% in the soil water estimated by the equilibration curves described in Supplementary methods. The factor aw represents the assimilation efficiency of deuterium into fatty acids and it has been estimated at a value of 0.71 for heterotrophs (35,74). 'FA C' is the C concentration of the respective fatty acid (average of labelled and natural abundance sample) calculated relative to the known amount of C of the internal standard 19:0.…”
Section: Ovapor-sipmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only does the rate of microbial growth represent a geochemical transformation, but it is also a parameter that microorganisms modulate in response to changing conditions: microorganisms may more readily replicate when conditions are favorable to them and adopt alternative physiologic states under adverse conditions. Methods for measuring microbial growth often rely upon the addition of an isotopically labeled substrate to a natural sample and measuring its incorporation into microbial biomass, a method generally termed stable isotope probing (SIP) (1)(2)(3). SIP has been applied with the stable isotopes of various elements including H, C, N, O, S, etc., through measurement of single-cells (4)(5)(6)(7)(8), membrane lipids (3,9,10), and nucleic acids (2,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%